2016
DOI: 10.1017/s0305000916000519
|View full text |Cite
|
Sign up to set email alerts
|

Words are not enough: how preschoolers’ integration of perspective and emotion informs their referential understanding

Abstract: When linguistic information alone does not clarify a speaker's intended meaning, skilled communicators can draw on a variety of cues to infer communicative intent. In this paper, we review research examining the developmental emergence of preschoolers' sensitivity to a communicative partner's perspective. We focus particularly on preschoolers' tendency to use cues both within the communicative context (i.e. a speaker's visual access to information) and within the speech signal itself (i.e. emotional prosody) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 106 publications
(146 reference statements)
1
7
0
Order By: Relevance
“…When the speaker asked for “the glass”, children had to integrate the semantics of the utterance with the speaker’s visual perspective to correctly infer which of the glasses the speaker was referring to. This study advanced our understanding by documenting that preschoolers use both information sources, a finding confirmed by a variety of other work 26 , 29 , 31 . Yet these studies neither specify nor test the process by which children integrate different information sources.…”
Section: Mainsupporting
confidence: 77%
“…When the speaker asked for “the glass”, children had to integrate the semantics of the utterance with the speaker’s visual perspective to correctly infer which of the glasses the speaker was referring to. This study advanced our understanding by documenting that preschoolers use both information sources, a finding confirmed by a variety of other work 26 , 29 , 31 . Yet these studies neither specify nor test the process by which children integrate different information sources.…”
Section: Mainsupporting
confidence: 77%
“…Resches and Pérez Pereira (2007) point out that ‘the capacity to take into account mental states in others seems to be a key factor which regulates communicative interchanges’ (p. 22). They showed that children with higher level ToM abilities were more adept at regulating communication (see also Graham, San Juan, & Khu, 2017; Roby & Kidd, 2008; Sidera, Perpiñà, Serrano, & Rostan, 2018 for the relationship between Theory of Mind and referential communication) since they were able to understand and anticipate the behaviors of others. While their results were based on production, we might assume that intonation and facial gesture would be some of the cues children might exploit in order to assess and ultimately predict the behavior of another individual in conversation.…”
Section: Discussionmentioning
confidence: 99%
“…Early language proficiency is a critical developmental skill given its stability from infancy through adolescence (Bornstein, Hahn, Putnick, & Suwalsky, ), and its role as a mediator in the development of other cognitive processes in early childhood (Graham, San Juan, & Khu, ; Wade, Browne, Plamondon, Daniel, & Jenkins, ). Early language has spillover effects in multiple domains of childhood and adulthood adaptive functioning, including achievement (Duncan et al, ; Scarborough, Neuman, & Dickinson, ), psychiatric problems (Beitchman et al, ; Cannon et al, ) and educational/occupational outcomes (Johnson, Beitchman, & Brownlie, ).…”
Section: The Importance Of Early Language Across the Lifespanmentioning
confidence: 99%